Early and Middle Pleistocene vegetation and its impact on faunal succession on the Liaodong Peninsula, Northeast China. (30th July 2021) - Shen, Hui; Zhao, Keliang; Ge, Junyi; Zhou, Xinying; Song, Yayun; Liu, Sizhao; Wang, Yuan; Jin, Changzhu; Gao, Chunling; Huang, Wenjuan; Li, Xiaoqiang
Abstract: Pollen evidence from a 25.3-m-long section ( 2.2–0.41 Ma) in the Jinyuan Cave, Liaodong Peninsula, indicates that from the Early–Middle Pleistocene, the climate showed a trend of gradual cooling and drying, with obvious fluctuations. The vegetation was represented by temperate broad-leaved forest from ca. 2.2 to 1.87 Ma, suggesting a relatively warm and humid climate. The period from 1.87 to 1.82 Ma witnessed an obviously cold and dry event, and coniferous and broadleaved mixed forests developed from 1.82 to 1.76 Ma. From 1.52 Ma to the Mid-Pleistocene Transition (MPT), the vegetation was dominated by forest steppe, and the climate became cold in the later stage. During the 0.59–0.41 Ma period, steppes developed, and the climate was cold and arid. At the same time, with climate variation, the faunal communities also changed obviously and co-evolved with vegetation types. In the early stage of the Early Pleistocene, the warm and humid climate was related to the presence of a wide range of thermophilous animals. From 1.7 to 1.5 Ma, the transition from forest to forest steppe might have promoted the emergence of certain grassland-adapted animals. During the MPT, grassland-adapted animals became dominant due to the flourishing forest steppe vegetation. The Middle Pleistocene witnessed the expansion of steppe and animals adapted to the arid grassland environment at that time.